Dampak Kebijakan Otonomi Khusus Terhadap Pengurangan Kemiskinan Di Provinsi Aceh - Ikhsan, Ikhsan; Pribadi, Ulung (Journal of Governance and Public Policy, 2015)
This study investigates the impact of autonomy special on poverty reduction. Special autonomy of Aceh designed torebuild Aceh after conflict and tsunami that had destroyed Aceh from the development and social political causingincreased poor people. Special autonomy expected to be the solution of social problems and poverty in aceh province.To achieve a purpose of this research, used the theory decentralization asymmetrical that helps to see effortsthe implementation of decentralization at the provincial level in accordance with local knowledge to the problem ofcommunity social and confinement the level of poverty. This research uses the method the qualitative study by adoptingdescriptive aimed at to explain deeper on the impact of autonomy special on poverty reduction through techniqueobservation, interviews and documentation.